Continuous Leakage‐Resilient Identity‐Based Encryption Scheme with CCA Security. Issue 4 (1st July 2019) - Zhou, Yanwei; Yang, Bo
Abstract : Leakage of private information including private key has become a threat to the security of computing systems. It has become a common security requirement that a cryptographic scheme should withstand various leakage attacks, including continuous leakage attacks. In order to obtain an Identity‐based encryption (IBE) scheme which can keep its original security in the continuous leakage setting, we propose a new construction method of IBE scheme with Chosen‐ciphertext attacks (CCA) security, which can tolerate continuous leakage attacks on many private keys of each identity, and whose security is proved based on the hardness of the classical Decisional bilinear Diffie‐Hellman (DBDH) assumption in the standard model. The leakage parameter is independent of the plaintext space and has the constant size.